A combined experimental and TDDFT-DFT investigation of structural and optical properties of novel pyrazole-1, 2, 3-triazole hybrids as optoelectronic devices. (2nd November 2021) - El Azab, I. H.; Ibrahim, A.; Abdel El-Moneim, M.; Zoromba, M. Sh.; Abdel-Aziz, M. H.; Bassyouni, M.; Al-Hossainy, A. F.
ABSTRACT: A conjugated semiconductor thin film of 1-((3-(3-(3, 5-diphenyl-4, 5-dihydro-1H-pyrazol-1-yl)-5-methyl-1H-1, 2, 4-triazol-1-yl)-1-phenyl-1H-pyrazol-4-yl)methyl)-4-phenyl-1H-1, 2, 3-triazole [4ph-TAzole] TF was synthesized. The fabricated [4ph-TAzole] TF thin film with a thickness of 150 ± 3 nm is manufactured by physical vapor deposition technique (PVD) at a low deposition rate with basic pressure of the chamber was 5 × 10 −5  mbar. Using DFT-TDDFT simulation, the structure measurements the energy gap, and optical properties were determined. The obtained DFT-TDDFT data provide good proof for the electronic transition in zero-dimensional [4ph-TAzole] TF as a single crystal molecule. This study provides valuable information on the nature and sources of defect formation and electronic transition in conductor organic derivate of triazole which opens the way for the application as an optoelectronic device.